Characterization of 304L laser welds using digital image correlation and x-ray computed tomography. (29th June 2021) - Jin, Helena; Madison, Jonathan D; Foulk, James W; Nelson, Kevin; Murawski, Scott G
Abstract: 304L stainless steel partial-penetration laser welds with varying penetration depths are needed for a variety of national security applications. Their mechanical performance depends on many parameters including weld schedule, penetration depth, and weld porosity. Unfortunately, these parameters are not easily divorced from one another as each has varying impacts upon the others. Therefore, an understanding of the interplay between these parameters as well as their impact on weld performance is rather useful. In this work, partial penetration laser welds are produced with four varying penetration depths at two different weld schedules. Mechanical testing is conducted to characterize the mechanical performance while full-field digital image correlation (DIC) is applied during testing to obtain the displacement field down to the micron-scale to better understand both global and local deformation behavior. Porosity of these welds is also investigated using x-ray computed tomography (XCT) prior to mechanical testing. The integration of DIC and XCT techniques with mechanical testing provides an expanded experimental dataset to evaluate the variations in mechanical response as a function of penetration depth, weld schedule and porosity. These experimental techniques also provide a promising approach for future study of laser performance.